OPEN BANKING SYSTEM- BOON OR BANE - Sujith Kumar SH (EPRA International Journal of Economic and Business Review(JEBR), 2022)
The world of Finance has changed. Latest innovations, made banks shifting from traditional banking system to smart banking system. The old banking system go to the bank have been replace by modern mechanisms that enabled the account holders to carry out the transactions from anywhere. Open banking system is already implemented in country like USA etc. implemented successfully. In India banking sector gradually opening to Open banking System. India Bank population covered over 80% of the Indian population. Majority of the population still reach out the branches for their account related works. Hence It required time and effort to bank branches to clear the doubts about the open banking facility and to educated the customers to utilize the benefit of Open banking System in India, otherwise it will be a bane to the banking industry.